Pengaruh Kepemilikan Publik, NPM, Solvabilitas, Dan Ukuran Perusahaan Terhadap Corporate Social Responsibility Pada Perusahaan Sektor Infrastruktur Yang Terdaftar di BEI - Novia Ardiana; Ajeng Tita Nawangsari (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
The principal emphasis of this study lies in evaluating the influence exerted by Public Ownership, Net Profit Margin (NPM), Solvency, and the contribution of organizational magnitude to CSR disclosure practices. Quantitative data were acquired in this study by means of analyzing existing documents. The research population includes 70 business entities listed on the Indonesia Stock Exchange during the period of 2023-2024, with a total of 25 business entities used as samples through purposive sampling. The study utilized secondary data obtained from the official Indonesia Stock Exchange portal (www.idx.co.id) as well as the portals of each business entity. The influence between variables was assessed through multiple linear regression data analysis. The research findings indicate that the variables of public ownership level and company size show a significant impact with a positive relationship direction on the extent of CSR reporting practices. On the contrary, the Net Profit Margin (NPM) and solvency level variables have been proven not to show a significant impact on CSR practice reporting.